Estimation of induced abortions in Brazil: review of the indirect method calculation based on hospital admissions due to abortion complications - Rosa Maria Soares Madeira Domingues; Agatha Sacramento Rodrigues; Marcos Augusto Bastos Dias; Valéria Saraceni; Rejane Sobrinho Pinheiro; Cláudia Medina Coeli; Alberto Pereira Madeiro (Cadernos de Saúde Pública)
Abstract: This study aimed to present a new proposal for the calculation of estimates of induced abortion in Brazil using the indirect method, based on hospital admissions due to abortion complications applying the Guttmacher Institute methodology. Data from the Brazilian Hospital Information System of the Brazilian Unified National Health System (SIH/SUS, acronym in Portuguese) were used to identify hospital admissions due to abortion with public funding and from the Brazilian National Agency for Private Health Insurance and Plans (ANS, acronym in Portuguese) for admissions with supplementary health funding. Correction factors were used to exclude hospital admissions due to miscarriage by the woman’s age group, and data from the 2016 National Abortion Survey (PNA, acronym in Portuguese) were used to review the correction factor for complications that did not require hospitalization, based on the simulation of scenarios with different parameters of population coverage of healthcare plans and frequency of induced abortions in SUS and supplementary health patients. Using this new proposal, a total unsafe abortion rate of 8.7 per 1,000 women aged 10-49 was estimated for 2015, with 9.9 in SUS patients and 5,4 in supplementary health patients, and a total unsafe abortion ratio of 18.5 per 100 live births, with 21.1 in SUS patients and 11.2 in supplementary health patients. This new calculation proposal is an advance because it includes data about hospital admissions of supplementary health and a correction factor for complications that did not result in hospitalization using empirical data from the 2016 PNA. This factor is based on available data and is expected to be improved as new evidence is generated, especially evidence that reflects the specificities of the various regions of the country.